(untitled) (Damascus University Journal of agriculture sciences, 2026)
The research was conducted at the Agricultural Scientific Research Center in Hama Governorate during 2020 and 2021 to study the effect of foliar spraying with amino acids on the growth and productivity of the Qaisi olive tree variety. The Agroton foliar spray was applied at a concentration of 1 ml/L according to the following treatments: F0 control without spraying, F1 one spray before flowering, F2 one spray after fruit set, F3 one spray one month before harvesting, F4 one spray before flowering and after fruit set, F5 one spray after fruit set and one month before harvesting, F6 one spray before flowering, after fruit set, and one month before harvesting. Ground fertilization was also added according to the recommended fertilization rates. The results showed that foliar spraying had a significant effect on vegetative growth traits, with treatment F4 (one spray before flowering and after fruit set) outperforming other treatments in terms of shoot length and total chlorophyll content (6.08 cm and 1.58 mg/mL, respectively), compared to the control (4.75 cm and 1.37 mg/mL, respectively). Foliar spraying with amino acids had a positive effect on the total number of flowers per branch, with the treatment before flowering outperforming other treatments (199.97 flowers per branch compared to 164.19 flowers per branch in the control). The results also showed a clear superiority in tree productivity, especially in treatment F6 (one spray before flowering, after fruit set, and one month before harvesting), with an average tree productivity of 33.3 kg compared to 14.07 kg in the control. The oil content in the fruits was also higher in the treated groups, with treatment F6 achieving the highest net profit of 16005.18 SYP per tree, equivalent to 192062.16 SYP per hectare, an increase of 163.10% compared to the control.